STUDY ON USEFULNESS OF STUDYING THE GEOGRAPHICAL VARIATION IN HUMAN FACIAL FEATURES - Anil Kumar (International Journal of Multidisciplinary Research and Studies, 2021)
Variation may be found in many of the visible characteristics of humans, such as the form of the brow region and the nose, the color of the skin and the eyes, the diverse qualities of body hair, and the size and proportions of the body. Since Darwin’s time, there has been substantial discussion over the extent to which such diversity may be explained by genetic drift (neutral processes), local adaptation, or sexual selection. This discussion began with Darwin (1871). One strategy for determining the relative influence of neutral versus selective processes on the differentiation of human traits is to compare the relative amounts of within-population and between-population variance.